Targeted treatment of advanced ovarian cancer: spotlight on rucaparib - Pearre DC; Tewari KS (Dove Medical Press, 2018)
Diana C Pearre, Krishnansu S Tewari Division of Gynecologic Oncology, Department of Obstetrics & Gynecology, University of California, Irvine Medical Center, Orange, CA, USA Abstract: The last 2 years have ushered in a new era in ovarian cancer therapy with the US Food and Drug Administration’s (FDA) approval of poly-ADP ribose polymerase (PARP) inhibitors (PARPi). One of the deadliest cancers that women experience, ovarian cancer, is most often diagnosed in advanced stages. Although cytoreductive surgery and (platinum/taxane-based) chemotherapy can place the majority of patients into remission, most will experience a relapse of their disease in their lifetime. This has led to studies exploring the benefits and efficacy of maintenance treatment. This review will briefly discuss the history of maintenance therapy as well as focus on the FDA’s approval of rucaparib and its companion tumor profiling test, in the US. It will describe how women with deleterious mutations in the BRCA gene, through their inherent deficiency in homologous recombination, presented scientists with a target to exploit through a concept known as synthetic lethality. Not only did this lead to a targeted treatment for BRCA mutation carriers but for other patients with deficiencies in homologous recombination and, more broadly, also in platinum-sensitive patients. The focus of this review will be on rucaparib in the US, approved for both maintenance of platinum-sensitive recurrent ovarian cancer and treatment in the third-line setting and beyond. It has the broadest indication amongst the three PARPi in ovarian cancer. Furthermore, the ongoing trials using rucaparib in ovarian cancer and other disease types will be discussed. Keywords: BRCA, PARP inhibitor, targeted therapy, rucaparib, ovarian cancer